Perancangan Sistem Informasi Pengelolaan Data Aset Menggunakan Metodologi Rapid Application Developmen (RAD) - Fauyhi Eko Nugroho; Tiara Delfiana; Mahpud Mahpud; Rohmat Taufiq (Universitas Muhammadiyah Tangerang, 2026)
Asset data management at PT Yuasa Battery Indonesia is still carried out manually using paper-based records, which may lead to data entry errors, duplication, and delays in providing asset information. These issues highlight the need for an integrated and structured information system to improve the efficiency and accuracy of asset management. This study aims to design and develop a web-based asset data management information system using the Rapid Application Development (RAD) methodology. The research methods include observation, interviews, and literature study, with system requirements analyzed using the PIECES approach. The system design was developed using UML modeling (use case diagram, activity diagram, sequence diagram, and ERD) and implemented using CodeIgniter, PHP, MySQL, and XAMPP. System testing was conducted using the black box testing method to ensure that all functions operate according to requirements. The results show that the designed system facilitates digital and real-time recording, management, tracking, and reporting of asset data. In conclusion, the developed information system provides a solution to improve the effectiveness and efficiency of the company’s asset management. It is recommended that the system be implemented gradually and enhanced with data security features and automatic backup systems to ensure data accuracy and sustainability.